Study of TiAlN PVD Coating on Stamping Dies Used in Tinplate Food Package Production - Fernandes, Liliana (2020)
The food industry is increasingly demanding in terms of the quality and appearance of its product packages. The present study focuses on identifying the main wear mechanisms developed during the stamping process of these packages. During the stamping process, the presence of a tin layer on the surface of the sheet used creates difficulties in the stamping due to the transfer of material from the sheet to the tool, addition of the coefficient of friction, and premature wear of some surfaces of the tool where the contact is more pronounced. In order to understand and avoid these phenomena, a TiAlN coating deposited by a physical vapor deposition (PVD) process was used, which was studied in the laboratory to analyze the evolution of the friction force on the contact and to verify the reaction of the coating on contact with tinplate. Afterwards, the tool was coated and practical tests were performed on the stamping. The obtained results allow confirmation of a significant improvement of the wear behavior of the tool when provided with the coating and also verify that this coating presented better wear resistance than others previously tested in the same working conditions.